Peningkatan Perilaku Activity Of Daily Living (ADL) Pada Remaja Panti Asuhan Al-Munasaroh Melalui Pendekatan Cognitive Behavioral Therapy (CBT) - Stania Amanda; Irhamni Rahman (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine how behavior modification in orphanage adolescents through the Cognitive Behavioral Therapy (CBT) method can enhance awareness of hygiene and health, particularly at Al-Munasaroh Orphanage. The research adopts an action research or intervention-based approach using qualitative methods. It emphasizes the analysis of behavioral changes through direct field observations and in-depth interviews, focusing on the quality and impact of behavioral modification among adolescents. The intervention was designed to address the lack of awareness regarding personal hygiene, environmental cleanliness, and health routines commonly found in institutionalized adolescents. The study investigates the various factors that influence the success of behavior modification, including internal motivation, emotional regulation, and external support from caregivers, peers, and the living environment. The CBT-based modification process spanned 18 structured sessions, which included psychoeducation, cognitive restructuring, role-playing, habit formation, and reinforcement techniques. Additionally, environmental improvements and the availability of hygiene-related facilities were integrated to support the desired behavioral outcomes. Findings reveal significant changes in daily hygiene practices among participants, such as increased frequency of handwashing, tidiness in personal belongings, regular bathing, and active participation in cleaning shared spaces. The support of peers and caregivers played a crucial role in maintaining consistency and motivation. The study concludes that CBT is an effective method for fostering awareness and instilling sustainable hygiene behaviors in adolescents living in orphanages. Based on these results, recommendations are proposed for integrating CBT-based hygiene programs into routine care at orphanages to promote long-term behavioral change and health awareness.